2020
DOI: 10.1042/bsr20203107
|View full text |Cite
|
Sign up to set email alerts
|

Icariin inhibits the inflammation through down-regulating NF-κB/HIF-2α signal pathways in chondrocytes

Abstract: Articular cartilage injury or defect is a common disease and is mainly characterized by cartilage degradation because of chondrocyte inflammation. By now, there are no effective drugs and methods to protect articular cartilage from degradation. Icariin (ICA) is a typical flavonoid compound extracted from Epimedii Folium with anti-inflammatory and bone-protective effects. Our previous studies demonstrate that ICA up-regulates HIF-1α expression and glycolysis in chondrocytes and maintains chondrocyte phenotype. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…A study reported that icariin can inhibit NF-κB activation and nuclear translocation triggered by TNF-α, as well as reduce chondrocyte apoptosis and inflammation ( Mi et al, 2018 ). In addition, according to the study of Pengzhen Wang et al (2020) , icariin inhibited the activation of NF-κB and HIF-2α in the chondrocytes of OA mice and attenuated the inflammatory response driven by TNF-α. In addition, the expression of MMPs was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that icariin can inhibit NF-κB activation and nuclear translocation triggered by TNF-α, as well as reduce chondrocyte apoptosis and inflammation ( Mi et al, 2018 ). In addition, according to the study of Pengzhen Wang et al (2020) , icariin inhibited the activation of NF-κB and HIF-2α in the chondrocytes of OA mice and attenuated the inflammatory response driven by TNF-α. In addition, the expression of MMPs was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…et Zucc.) Maxim., Epimedium pubescens Maxim., or Epimedium koreanum Nakai), is a typical flavonoid compound with antiinflammatory, anti-oxidative (Zuo et al, 2019), and boneprotective properties (Wang et al, 2020). ICA can treat OA through multiple pathways and targets.…”
Section: Icariinmentioning
confidence: 99%
“…ICA can treat OA through multiple pathways and targets. It increases the vitality of chondrocytes through reducing the inflammatory damage caused by NF-κB/HIF-2α signaling (Wang et al, 2020); regulates chondrocyte autophagy by mediating the PI3K/Akt/ mTOR pathway (Tang et al, 2021) and inhibiting NF-κB; alleviates OA by inhibiting inflammatory cytokines and chondrocyte apoptosis (Liu et al, 2018a;Mi et al, 2018); upregulates the proliferation, osteogenic, and chondrogenic differentiation of bone marrow-derived MSCs (BMSCs); and protects BMSCs from apoptosis through the mitogen-activated protein kinase (MAPK) signaling pathway (Liu et al, 2020a). In a study on ICA and human OA fibroblast-like synoviocytes, it was found that ICA could inhibit the expression of IL-1β, MMP4, and glucose-regulated protein 78 (GRP78), which further reduces the inflammatory response (Pan et al, 2017).…”
Section: Icariinmentioning
confidence: 99%
“…By the analysis of cultured HIF-2α-deficient ECs Skuli et al did, the mechanism of HIF-2α regulating the process of pathological angiogenesis and revascularization may be related to HIF-2α-dependent expression of specific angiogenic factors, which involve angiopoietin 2, a Notch ligand and delta-like ligand 4 (Dll4) (15). HIF-2α directly or indirectly regulates the expression of many genes, the induced genes involving angiogenesis are upregulated, such as basic fibroblast growth factor (bFGF) (16), vascular endothelial growth factor A (VEGF-A) (17), and tumor necrosis factor alpha (TNF-α), platelet-derived growth factor (PDGF) (18), extracellular matrix (ECM) also plays a certain role in angiogenesis, and MMPs is one of the main proteases involved in ECM degradation, HIF-2α can also promote angiogenesis by regulating the expression of MMPS (19).…”
Section: Hif-2α and Angiogenesismentioning
confidence: 99%